Maximizing M and A Success through Contract Lifecycle Management : A Strategic Approach to Due Diligence and Integration - Niraj Ittan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the transformative impact of Contract Lifecycle Management (CLM) systems on mergers and acquisitions processes, focusing on their role in enhancing due diligence and post-merger integration. The article explores how integrating artificial intelligence, blockchain technology, and natural language processing has revolutionized contract management throughout the M&A lifecycle. By analyzing various aspects, including pre-merger contract portfolio assessment, streamlined due diligence processes, risk mitigation strategies, and value discovery mechanisms, this article demonstrates the comprehensive benefits of modern CLM implementations. The article encompasses multiple dimensions of contract management automation, from centralized repository benefits to organizational efficiency improvements. Through examination of real-world implementations across diverse industries, the article highlights the crucial role of CLM systems in reducing processing times, enhancing accuracy, improving compliance management, and facilitating successful post-merger integration. This article provides valuable insights into the strategic importance of CLM systems in modern M&A operations and their impact on organizational success.